Moderate hypothermia in the management of resistant automatic tachycardias in children. Issue 3 (September 1991) - Balaji, S; Sullivan, I; Deanfield, J; James, I
Abstract : BACKGROUND--Automatic focus tachycardias are often resistant to electrical and pharmacological treatment. Moderate systemic hypothermia (32-34 degrees C) may reduce the tachycardia rate in children with His bundle tachycardia after cardiac surgery. METHODS--The case notes of seven children with automatic focus tachycardias treated with hypothermia were reviewed. Six had His bundle tachycardia after cardiac surgery and one had ectopic atrial tachycardia; all had signs of low cardiac output. RESULTS--Hypothermia led to a reduction in heart rate in all patients (from 211 (28) (mean (SD] to 146 (5) beats/minute, p less than 0.001), with rises in systolic blood pressure (from 74 (14) mm Hg to 97 (10) mm Hg, p less than 0.01) and hourly urine output (from 0.5 (0.4) ml/kg to 4.6 (2.8) ml/kg, p less than 0.02). No direct adverse effects were noted. The arrhythmia did not resolve in three children, who died (two with His bundle tachycardia after Fontan procedures and one with ectopic atrial tachycardia); the other four regained sinus rhythm which was maintained at follow up of 3-13 (mean 9) months. CONCLUSIONS--Moderate systemic hypothermia led to slowing of the arrhythmia rate and an improvement in cardiac output in patients with resistant automatic focus tachycardias. It can be used to improve the haemodynamic condition while other measures of arrhythmia control are being pursued or until spontaneous recovery of normal rhythm.